Pengelolaan Kearsipan Siswa Dalam Meningkatkan Mutu Layanan Administrasi Di Sekolah Dasar - Purnamasari, Indah; Saputra, Ade Akhmad (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
Student archive management is a contributing factor to the quality improvement of school administrative services. The purpose of this study is to understand effective management of student archives and how it can improve the quality of administrative services in SD Negeri 6 Air Kumbang. My research method was descriptive qualitative. The data sources in this research are the Principal, Administrative Staff, Teachers and Students of SD Negeri 6 Air Kumbang. The methods of data collection in this study used observation, interview and documentation approaches. The method of data analysis in this study is performed by data reduction, data presentation, and conclusion drawing. The results of this study indicate that archive management include archive creation procedures and archive storage procedures. Student records include academic, administrative, and student development information that should be managed in the best possible manner to ensure easy availability as well as integration into decision-making. Archives have an important role in ensuring smooth school administration operations, and therefore archives are essential to be maintained as they will be required in the long run.